Language Warrior's Manifesto : How to Keep Our Languages Alive No Matter the Odds - Treuer, Anton (Book collections on Project MUSE., 2020)
"Anton Treuer has been at the forefront of the battle to revitalize Ojibwe for many years. In this impassioned argument, he discusses the interrelationship between language and culture, the problems of language loss, strategies and tactics for resisting, and the inspiring stories of successful language warriors. He recounts his own single-minded and sometimes hilarious struggle to learn Ojibwe as an adult, and he depicts the astonishing success of the language program at Lac Courte Oreilles in northern Wisconsin, where dedicated families and teachers have raised a hundred children who speak Ojibwe as their first language. This is a manifesto, a rumination, and a rallying cry for the preservation of priceless languages and cultures"--